2021
DOI: 10.3390/molecules26092432
|View full text |Cite
|
Sign up to set email alerts
|

Screening a Strain of Klebsiella sp. O852 and the Optimization of Fermentation Conditions for Trans-Dihydrocarvone Production

Abstract: Flavors and fragrances have high commercial value in the food, cosmetic, chemical and pharmaceutical industries. It is interesting to investigate the isolation and characterization of new microorganisms with the ability to produce flavor compounds. In this study, a new strain of Klebsiella sp. O852 (accession number CCTCC M2020509) was isolated from decayed navel orange (Citrus sinensis (L.) Osbeck), which was proved to be capable of converting limonene to trans-dihydrocarvone. Besides, the optimization of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…O852 is capable of converting limonene to carveol, carvone and dihydrocarvone, oxidizing carveol to carvone and dihydrocarvone, and catalyzing carvone to form dihydrocarvone. 14,19 In another report, the synthesis of carveol and dihydrocarvone by asymmetric reduction of carvone was performed using ketoreductases and ene-reductases, respectively. Dihydrocarvone obtained was further converted into dihydrocarveol catalyzed by ketoreductases.…”
Section: Biosynthetic Pathway Of Spearmint Aromatic Moleculesmentioning
confidence: 99%
See 3 more Smart Citations
“…O852 is capable of converting limonene to carveol, carvone and dihydrocarvone, oxidizing carveol to carvone and dihydrocarvone, and catalyzing carvone to form dihydrocarvone. 14,19 In another report, the synthesis of carveol and dihydrocarvone by asymmetric reduction of carvone was performed using ketoreductases and ene-reductases, respectively. Dihydrocarvone obtained was further converted into dihydrocarveol catalyzed by ketoreductases.…”
Section: Biosynthetic Pathway Of Spearmint Aromatic Moleculesmentioning
confidence: 99%
“…The aromatic molecules of spearmint essential oil are widely used in the industry, mainly as aroma in food (bakery product, candy, chewing gum, beverages, condiments) and as fragrance in cosmetics and toiletries (fragrances, shampoos, toilet soaps, toothpaste). 13,14,154 It is reported that the global market of aromas and fragrances including spearmint aromatic molecules (carvone, USD 350 L −1 ; carveol, USD 529 L −1 ) has reached US$ 28.2 billion in 2017, marking an increase of 4.6% as compared with 2016. It is expected that the market is growing at 4.9% per annum to reach approximately US$ 36 billion in 2022.…”
Section: Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…The dihydrocarvone biosynthetic pathway and related enzyme genes have been studied and elucidated. To the best of our knowledge, dihydrocarvone could be yielded by carvone hydrogenation or limonene oxidation 14 . Oxidation of limonene to dihydrocarvone can occur via three enzymatic steps, with carveol and carvone as intermediate products 15 .…”
Section: Introductionmentioning
confidence: 99%